The Effect of Unemployment Benefit Generosity on Unemployment Duration: Quasi-Experimental Evidence from Slovenia - Matija Vodopivec; Suzana Laporsek; Primož Dolenc; Milan Vodopivec (Institute for the Study of Labor (IZA), 2015)
The paper analyses the effects of a 2011 increase in the unemployment benefit replacement rate on the job-finding rate of Slovenian benefit recipients. Using registry data on the universe of Slovenian unemployment benefit recipients, we exploit legislative changes that selectively increased the replacement rates for certain groups of workers while leaving them unchanged for others. Applying this quasi-experimental approach, we find that increasing the replacement rate significantly decreased the hazard rate of the transition from unemployment to employment, with an implied elasticity of the hazard rate with respect to benefit replacement rate being 0.7 to 0.9. The results also show that the increase of the unemployment benefit replacement rate does not affect the job-finding probability of jobseekers whose reason for unemployment is employer exit, and that the effects of the increase of replacement rate are present only upon exit to employment and not to inactivity.
Keywords: J64; J65; 330; unemployment insurance; unemployment benefit replacement rate; job-finding rate